2020
DOI: 10.1172/jci.insight.141246
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intolerance and rapid skeletal muscle energetic decline in human age-associated frailty

Abstract: BACKGROUND Physical frailty in older individuals is characterized by subjective symptoms of fatigue and exercise intolerance (EI). Objective abnormalities in skeletal muscle (SM) mitochondrial high-energy phosphate (HEP) metabolism contribute to EI in inherited myopathies; however, their presence or link to EI in the frail older adult is unknown. METHODS Here, we studied 3 groups of ambulatory, community-dwelling adults with no history of significant coronary disease: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…The HF cohort in this study was significantly older than the control cohort, with a mean age difference of 20 years. In addition, normal aging induces a shift in skeletal muscle metabolism in the form of sarcopenia 37 , 38 , the effect of which may be a contributor to the results seen here given the age difference between the cohorts. Increasing age of the HF cohort increases the likelihood of multiple co-morbidities including hypertension and coronary heart disease.…”
Section: Discussionmentioning
confidence: 81%
“…The HF cohort in this study was significantly older than the control cohort, with a mean age difference of 20 years. In addition, normal aging induces a shift in skeletal muscle metabolism in the form of sarcopenia 37 , 38 , the effect of which may be a contributor to the results seen here given the age difference between the cohorts. Increasing age of the HF cohort increases the likelihood of multiple co-morbidities including hypertension and coronary heart disease.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, the frail and prefrail groups had PCr recovery that was 57 and 20 seconds slower, respectively, than for the nonfrail group. A recently published study shows rapid energetic decline in the exercised skeletal muscle of frail compared to nonfrail older adults, further demonstrating stress-induced energy dysfunction in frailty 51 . Stress-response system, HPA axis.…”
Section: Physical Frailty Is An Emergent State Of a Compromised Complmentioning
confidence: 89%
“…Evidence of mitochondrial energy production deficits exists in both humans and a mouse model of frailty 28,84 . In humans, PCr recovery time, a measure of mitochondrial oxidative phosphorylation, is reduced 50,51 . In a mouse model of frailty derived through chronic inflammation, skeletal muscle ATP kinetics are impaired and decreased mitochondrial degradation in skeletal muscle has been identified 28,85 .…”
Section: Potential Drivers Of the Complex System Dysregulation Underlmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of skeletal muscle mass with aging, which is known as sarcopenia, diminishes muscle strength and exercise capacity, which seriously affects the quality of life of elderly people and is a major sign of age-associated frailty [ 1 , 2 ]. While regular physical exercise is the best and only way to maintain skeletal muscle mass, a recent study reported that exercise intolerance and rapid skeletal muscle energetic decline during exercise are characteristics of age-associated frailty [ 3 ], suggesting that when an elderly person begins to suffer from exercise intolerance, a vicious circle is started in which reduction in skeletal muscle mass leads to further deterioration of exercise intolerance. Increasing exercise endurance capacity by improving skeletal muscle energy metabolism is expected to be an effective means of breaking this vicious cycle.…”
Section: Introductionmentioning
confidence: 99%